การจัดเส้นทางที่เหมาะสมในโครงข่ายสื่อสารแบบคอนเนกชั่นโอเรียนเตด โดยใช้ฮิวริสติกอัลกอริทึม - วาทิต เบญจพลกุล (จุฬาลงกรณ์มหาวิทยาลัย, 1998)
This research proposes an optimum semi-static virtual circuit routing method in connection-oriented communication network using Heuristic Algorithm, developed from Genetic Algorithm, Tabu Search, and Evolutionary Computing. The routing constraints are the probability of packet loss in virtual circuit due to the blocking of packet at the switch output buffer. This research also proposes a method to assign initial solution, used to search the optimum point of Heuristic Algorithm. The initial solution is assigned by either a set of virtual circuit route, obtained from minimum hop route technique or from least load route one. Tested result of optimum virtual circuit routing using the proposed Heuristic Algorithm for any network sizes shows that the routes obtained are better than those obtained from minimum hop route and least load route techniques. In this research, the comparison results of the number of iteration in calculation for Heuristic Algorithm in which the number of mother vectors and the number of son vectors are assigned by several values show that when the number of mother vectors and the number of son vectors are increased, the number of iteration is decreased.